Differentiated Community Engagement Approaches but same mission: University Outreach programs in Africa - Nampala, M.P. (African Journal of Rural Development (AFJRD), 2017)
The African Journal of Rural Development (AFJRD) is a peer-reviewed scholarly journal which by nature of its scope (rural development) publishes articles from a diversity of themes and disciplines with perspectives on the well-being of rural livelihoods. The papers published in this Issue (Volume 3, Issue 2) fall within the broad thematic categories of (a) Agricultural Extension and Advisory Services, (b) Natural Resources Management, (c) Biotic and Abiotic factors, (d) Circular Economy. These are very topical themes in the discourse on food and nutrition security for rural development. Dissemination of knowledge and innovations on those themes is important for promoting socio-economic development. This is especially important since the most dominant theme in agricultural research for development (AR4D) is usually agricultural productivity which responds to only one dimension of food and nutritional security, namely, food availability. The papers in this issue depict research for development that does not only address food availability but the other aspects, of food access, food stability and food utilization as well as dimensions of food and nutritional security. Optimistically, the readership will find these intriguing, thought-provoking and useful for catalysing further research for development to generate new knowledge and innovations to be deployed in rural development interventions.
Keywords: Agricultural research for development; Peer-reviewed; Rural development; Scholarly journal